Noncontinuous Positive Airway Pressure Therapies for Obstructive Sleep Apnea - Jones, Shirley F.; Brito, Veronica (Seminars in Respiratory and Critical Care Medicine, 2014)
While continuous positive airway pressure is the first-line treatment for obstructive sleep apnea, many patients find this form of therapy undesirable leading to treatment nonadherence. Both mandibular advancement devices and surgical therapy offer alternative solutions for such patients. This article serves to compare the types of surgical interventions and mandibular advancement devices available, their mechanisms of action, and expected side effects. Emphasis is made on the limitations and challenges in the interpretation of the available literature due to the varying definitions of curative success. The effects of mandibular advancement devices and surgical therapy on the apnea–hypopnea index and oxygen saturation are reviewed. Patient-centered outcomes of sleepiness, quality of life, treatment preference, adherence, and their effects on disease-related outcomes of hypertension are summarized. When available, comparative effectiveness trials between these therapies versus continuous positive airway pressure are emphasized. Patient selection criteria, practice parameters, and treatment limitations are discussed.
Keywords: obstructive sleep apnea; oral appliances; mandibular advancement device; surgery; uvulopalatopharyngoplasty; tongue; tonsils; nasal surgery